Fresno County Bar Association Luncheon with Justice Cruz Reynoso - Watkins, Howard::::::::: (1982)
TV Channel 30 reporter interviewing Justice Reynoso; Gloria Hernandez; Back Row: ?, Justice Reynoso, Hon. Armando Rodriguez